Identification of Anticoagulation Benefit Subgroups of Patients With Left Ventricular Thrombus - Zechen Liu; Boqun Shi; Rui Zhang; Kefei Dou; Weihua Song (Reviews in Cardiovascular Medicine)
Background: Left ventricular thrombus (LVT) is associated with major adverse cardiovascular and cerebrovascular events (MACCEs). Anticoagulation represents the current primary management for LVT; however, current studies in some Asian populations suggest that the anticoagulation benefit in LVT patients is not significant. Given the heterogeneity of clinical phenotypes in LVT patients, the population of LVT patients who benefit from anticoagulation needs to be further explored. Methods: This study included patients diagnosed with LVT at the FuWai Hospital from 2009 to 2021. We performed a latent class analysis (LCA) based on important clinical characteristics to objectively determine the number and dimensionality of clusters. Additionally, Kaplan–Meier curves and a Cox analysis were used to explore the relationship between anticoagulation therapy and MACCEs and major bleeding events in LVT patients. Results: A total of 1085 patients were enrolled in this study, and during a median follow-up time of 36.5 months, 206 patients developed MACCEs, while 16 patients developed major bleeding events. Moreover, 1085 patients were categorized into four clusters following the LCA. In the adjusted model, the risk of MACCEs was significantly lower in LVT patients receiving anticoagulation in cluster 4 (hazard ratio (HR): 0.486, 95% confidence interval (CI): 0.243–0.971) than in the group not receiving anticoagulation; however, there were no differences in the other three clusters or the whole population. There was a significant interaction between anticoagulation and the clustered subgroups (p for interaction in MACCEs: 0.046). However, no significant correlation was found for major bleeding events across clusters or for anticoagulant therapy. Conclusions: Our study suggests that not all LVT patients benefit from anticoagulation therapy; younger LVT patients with fewer complications and more cardiomyopathies are more likely to benefit from anticoagulation therapy.